Adjusting Historical Costs for Inflation with the Use of Standardized Automated Tools - Guertin JR; Chouinard NH; Forget A; Blais L (Dove Medical Press, 2024)
Jason Robert Guertin,1- 3 Naomi Hope Chouinard,1- 3 Amélie Forget,4,5 Lucie Blais4,5 1Centre de recherche du CHU de Québec-Université Laval, Quebec City, Canada; 2Department of Social and Preventive Medicine, Faculty of Medicine, Université Laval, Quebec City, Canada; 3Centre de recherche en organogénèse expérimentale de l'Université Laval/LOEX, Quebec City, Canada; 4Faculty of Pharmacy, Université de Montréal, Montréal, Canada; 5Centre de recherche du Centre intégré universitaire de santé et de services sociaux du Nord-de-l'Île-de-Montréal, Montréal, CanadaCorrespondence: Jason Robert Guertin, Centre de recherche du CHU de Québec - Université Laval, Hôpital du Saint-Sacrement, 1050 Chemin Sainte-Foy, Local J1-11, Quebec City, G1S 4L8, Canada, Tel +1 418-682-7511 ext 82516, Email jason.guertin@fmed.ulaval.ca